Effects of Ionizing Radiation on the Biophysical Properties of Type I Collagen Fibrils - Kester Ng; Nader Allam; Mehrnoosh Neshatian; Mina Vaez; Liisa M. Hirvonen; Ernest Lam; Alex Vitkin; Laurent Bozec (PLoS ONE, 2025)
Ionizing radiation is extensively employed in both diagnostic and therapeutic medical practices. The impact of this radiation on collagen, a primary structural protein in humans, remains underexplored, particularly at varying doses and hydration states. This study explores the impact of ionizing radiation on type I collagen fibrils at three radiation doses (diagnostic, therapeutic, and sterilization) and under two hydration conditions using an engineered acellular collagen membrane to reflect varying biological conditions. Techniques including atomic force microscopy (AFM), fluorescence lifetime imaging microscopy (FLIM), and Attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR) were utilized to assess changes in mechanical properties, biochemical stability, and molecular structure respectively. Our results demonstrate that ionizing radiation alters the mechanical properties of collagen fibrils, notably indentation modulus, which reflects changes in stiffness or elasticity. These modifications depended on the hydration state at the time of radiation exposure; hydrated fibrils typically exhibited increased stiffness, suggesting enhanced cross-linking, whereas dehydrated fibrils showed reduced stiffness, indicative of structural weakening, possibly due to bond breakdown. Morphological changes were minimal, suggesting that radiation primarily affects the internal structure rather than the overall appearance of the fibrils. Biochemically, variations in fluorescence lifetimes highlighted changes in the collagen’s biochemical environment, dependent on the dose and hydration state. Despite these biochemical and mechanical changes, FTIR analysis indicated that the primary structure of collagen was largely preserved post-irradiation for all examined dose levels. These findings imply that radiation can modify the mechanical properties of collagen, potentially affecting tissue integrity in clinical settings. This could influence the management of radiation-induced conditions like osteoradionecrosis, fibrosis and cancer metastasis. Overall, our study underscores the need for further research into the effects of radiation on structural proteins to better understand and mitigate radiation-induced tissue damage.